Numerical Simulation for Fracture Propagation in Elastoplastic Formations. (26th August 2021) - Hu, Yafei; Zhao, Jin; Cao, Lihu; Zhao, Jinzhou; Li, Junshi; Wu, Zhiying; Hou, Jianfeng
Abstract : Current hydraulic fracture models are mainly based on elastic theories, which fail to give accurate prediction of fracture parameters in plasticity formation. This paper proposes a fluid–solid coupling model for fracture propagation in elastoplastic formations. The rock plastic deformation in the model satisfies the Mohr-Coulomb yield criterion and plastic strain increment theory. The extended finite-element method (XFEM) combined with the cohesive zone method (CZM) is used to solve the coupled model. The accuracy of the model is validated against existing models. The effects of stress difference, friction angle, and dilation angle on fracture shape (length, width), injection pressure, plastic deformation, induced stress, and pore pressure are investigated through the model. The results indicate that compared with elastic formation, fracture propagation in elastoplastic formation is more difficult, the breakdown pressure and extending pressure are greater, and fracture shape is wider and shorter. The plastic deformation causes the fracture tip to become blunt. Under the condition of high stress difference or low friction angle formation, it is prone to occur large plastic deformation zones and form wide and short fracture. Compared with friction angle, dilation angle is less sensitive to plastic deformation, fracture parameters, and fracture geometry. For the formation with high stress difference and friction angle, the effect of plasticity deformation on fracture propagation should not be ignored.